Question
upstudy study bank question image url

19. \( \int_{3}^{3}\left(x^{2}+2 x-4\right) d x=\left[\frac{1}{3} x^{3}+x^{2}-4 x\right]_{1}^{3}=(9+9-12)-\left(\frac{1}{3}+1-4\right)=6+\frac{4}{3}=\frac{29}{3} \) 21. \( \int_{0}^{2}\left(\frac{4}{5} t^{3}-\frac{4}{4} t^{2}+\frac{2}{5} t\right) d t=\left[\frac{1}{3} t^{4}-\frac{1}{4} t^{3}+\frac{4}{8} t^{2}\right]_{0}^{2}=\left(\frac{4}{5}-2+\frac{4}{5}\right)-0=2 \) 23. \( \int_{1}^{3} \sqrt{x} d x=\int_{1}^{9} x^{1 / 2} d x=\left[\frac{x^{3 / 2}}{3 / 2}\right]_{1}^{3}=\frac{4}{4}\left[x^{3 / 2}\right]_{1}^{0}=\frac{4}{4}\left(9^{3 / 2}-1^{3 / 2}\right)=\frac{3}{3}(27-1)=\frac{24}{3} \) 25. \( \int_{\pi / 6}^{\pi} \sin \theta d \theta=[-\cos \theta]_{\pi / 6}^{\pi}=-\cos \pi-\left(-\cos \frac{\pi}{6}\right)=-(-1)-(-\sqrt{3} / 2)=1+\sqrt{3} / 2 \) 27. \( \int_{0}^{1}(u+2)(u-3) d u=\int_{0}^{1}\left(u^{2}-u-6\right) d u=\left[\frac{1}{3} u^{3}-\frac{1}{2} u^{2}-6 u\right]_{0}^{1}=\left(\frac{1}{3}-\frac{1}{2}-6\right)-0=-\frac{37}{6} \)

Ask by Zimmerman Vargas. in Yemen
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The integrals evaluate to the following: - **Problem 19**: \(0\) - **Problem 21**: \(\frac{46}{15}\) - **Problem 23**: \(2\sqrt{3} - \frac{2}{3}\) - **Problem 25**: \(1 + \frac{\sqrt{3}}{2}\) - **Problem 27**: \(-\frac{37}{6}\)

Solution

Let's go through each integral step by step, correcting any mistakes and ensuring clarity in the calculations. ### Problem 19 Evaluate the integral: \[ \int_{3}^{3}\left(x^{2}+2 x-4\right) d x \] 1. **Evaluate the definite integral**: Since the limits of integration are the same (from 3 to 3), the value of the integral is: \[ \int_{3}^{3} f(x) \, dx = 0 \] ### Problem 21 Evaluate the integral: \[ \int_{0}^{2}\left(\frac{4}{5} t^{3}-\frac{4}{4} t^{2}+\frac{2}{5} t\right) d t \] 1. **Find the antiderivative**: \[ F(t) = \left[\frac{1}{3} \cdot \frac{4}{5} t^{4} - \frac{1}{4} t^{3} + \frac{2}{5} \cdot \frac{1}{2} t^{2}\right] = \left[\frac{4}{15} t^{4} - \frac{1}{4} t^{3} + \frac{1}{5} t^{2}\right] \] 2. **Evaluate from 0 to 2**: \[ F(2) = \frac{4}{15} \cdot 16 - \frac{1}{4} \cdot 8 + \frac{1}{5} \cdot 4 = \frac{64}{15} - 2 + \frac{4}{5} \] Convert \(2\) to a fraction with a common denominator: \[ 2 = \frac{30}{15}, \quad \frac{4}{5} = \frac{12}{15} \] Thus, \[ F(2) = \frac{64}{15} - \frac{30}{15} + \frac{12}{15} = \frac{46}{15} \] And \(F(0) = 0\). 3. **Final result**: \[ \int_{0}^{2} \left(\frac{4}{5} t^{3}-t^{2}+\frac{2}{5} t\right) dt = \frac{46}{15} \] ### Problem 23 Evaluate the integral: \[ \int_{1}^{3} \sqrt{x} \, dx \] 1. **Find the antiderivative**: \[ F(x) = \left[\frac{2}{3} x^{3/2}\right] \] 2. **Evaluate from 1 to 3**: \[ F(3) = \frac{2}{3} \cdot 3^{3/2} = \frac{2}{3} \cdot 3\sqrt{3} = 2\sqrt{3} \] \[ F(1) = \frac{2}{3} \cdot 1^{3/2} = \frac{2}{3} \] 3. **Final result**: \[ \int_{1}^{3} \sqrt{x} \, dx = 2\sqrt{3} - \frac{2}{3} \] ### Problem 25 Evaluate the integral: \[ \int_{\pi / 6}^{\pi} \sin \theta \, d \theta \] 1. **Find the antiderivative**: \[ F(\theta) = -\cos \theta \] 2. **Evaluate from \(\frac{\pi}{6}\) to \(\pi\)**: \[ F(\pi) = -\cos(\pi) = 1 \] \[ F\left(\frac{\pi}{6}\right) = -\cos\left(\frac{\pi}{6}\right) = -\frac{\sqrt{3}}{2} \] 3. **Final result**: \[ \int_{\pi / 6}^{\pi} \sin \theta \, d \theta = 1 - \left(-\frac{\sqrt{3}}{2}\right) = 1 + \frac{\sqrt{3}}{2} \] ### Problem 27 Evaluate the integral: \[ \int_{0}^{1}(u+2)(u-3) \, du \] 1. **Expand the integrand**: \[ (u+2)(u-3) = u^2 - 3u + 2u - 6 = u^2 - u - 6 \] 2. **Find the antiderivative**: \[ F(u) = \left[\frac{1}{3} u^{3} - \frac{1}{2} u^{2} - 6u\right] \] 3. **Evaluate from 0 to 1**: \[ F(1) = \frac{1}{3} - \frac{1}{2} - 6 = \frac{1}{3} - \frac{3}{6} - \frac{36}{6} = \frac{1}{3} - \frac{39}{6} \] Convert \(\frac{1}{3}\) to sixths: \[ \frac{1}{3} = \frac{2}{6} \] Thus, \[ F(1) = \frac{2}{6} - \frac{39}{6} = -\frac{37}{6} \] 4. **Final result**: \[ \int_{0}^{1}(u+2)(u-3) \, du = -\frac{37}{6} \] ### Summary of Results - Problem 19: \(0\) - Problem 21: \(\frac{46}{15}\) - Problem 23: \(2\sqrt{3} - \frac{2}{3}\) - Problem 25: \(1 + \frac{\sqrt{3}}{2}\) - Problem 27: \(-\frac{37}{6}\)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

Have you ever thought about how integrals can represent areas? When you compute definite integrals, you’re really finding the area under a curve between two points on the x-axis! For example, the integral of \( x^2 + 2x - 4 \) from 3 to 3 is zero—because there’s no area when the limits are the same. In the realm of physics, integrals are everywhere! They're used to calculate quantities like distance, volume, and even work done. For instance, using integrals, you can find the work done by a variable force or determine the area under velocity-time graphs, showcasing how integral calculus isn't just academic, but a vital tool in understanding the real world.

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy